TEACHING ETHICS IN ACCOUNTING: APPROACHES AND CHALLENGES - Shahida Bt Shaharuddin; Nurul Nazlia Jamil (Journal of Islamic, Social, Economics and Development, 2022)
This paper aims to review the literature that discussing on the teaching approachesused in teaching ethics courses, especially in the accounting field. This paper also highlightsthe challenges associated with the teaching approaches. Given the influence of ethics educationon the ethical behavior of students, it is important to ensure the quality of ethics courses offeredin the university. One of the criteria that determines quality is by looking at its pedagogy. It isvital to set the objectives of the course before determine the teaching approaches. The goal ofthe ethics course is to develop moral awareness and moral sensitivity for the students. Due tothis, previous literature suggests accounting educators use active learning for teachingapproaches in the ethics course. This includes case studies, guest speakers, and groupdiscussions. Group discussions can be conducted using activities such as role-playing.However, there are challenges in using active learning in the pedagogy. The challenges aretime limitation, students’ participation, and creating a safe learning environment. This papercan help accounting educators to get ideas on appropriate teaching approaches in an ethicscourse.